Applying Situational Leadership to Redeployment Duties During COVID-19: Lessons Learned. Issue 4 (15th February 2022) - Nonaillada, Jeannine; Martin, Rob Armstrong
Abstract : Background and Objectives: In March 2020, the coronavirus disease-2019 (COVID-19) pandemic caused many disruptions to usual operations and demands in excess of normal capacity at NYU Langone Hospital Long Island and NYU Long Island School of Medicine. Significant increases in volume of critically ill patients necessitated hospital administrators to redeploy faculty physicians and other staff to support other areas as a way of exercising option value. This commentary describes our experiences as 2 medical school deans and teaching professors where we recently applied the model of situational leadership during our redeployment as unit clerks on newly-created COVID patient care units at the height of the COVID-19 pandemic in our local area. Our experience yielded personal feelings of accomplishment and allowed us to exercise nonlinear thinking, which we believe contributed to greater staff operational efficiency, using principles of situational leadership during these hospital redeployment initiatives. Key Takeaways: Situational leadership is an effective management model for hospital academic leaders who are not routinely in clinical operations to initiate in emergency conditions when unprecedented working scenarios and feelings of staff uncertainty are occurring, while option value is being exercised with faculty/staff redeployment. Our experience led to increased self-actualization. We provide recommendations to health care administrators on how to better prepare for future faculty/staff redeployments in the hospital.